Diaphragm, preparation method thereof and battery

By introducing a porous layer into the separator of the liquid lithium metal battery, the combination of polymer solid electrolyte and oxide solid electrolyte is used to improve the mechanical strength and lithium ion conductivity of the separator, the problem of lithium dendrites piercing the separator is solved and the cycle life of the battery is extended.

CN119890615AActive Publication Date: 2025-04-25SHENZHEN INX ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510351118.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-25
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The existing liquid lithium metal batteries may cause the separator to be pierced due to the growth of lithium dendrites, which in turn causes problems of short circuits and short cycle life.

Method used

A separator is provided, which includes a base film and a porous layer located on at least one surface of the base film. The porous layer comprises a polymer solid electrolyte and an oxide solid electrolyte. The oxide solid electrolyte is dispersed in the polymer solid electrolyte in a particle form, and holes and pores are formed in the polymer solid electrolyte to enhance the mechanical strength and lithium ion conductivity of the membrane.

Benefits of technology

By enhancing the mechanical strength of the diaphragm and improving the lithium ion transmission path, the risk of lithium dendrites is reduced, the cycle life of the battery is extended, and the heat resistance of the diaphragm is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890615A_ABST
    Figure CN119890615A_ABST
Patent Text Reader

Abstract

The invention relates to a diaphragm, a preparation method thereof and a battery. The diaphragm comprises a base membrane and a porous layer located on at least one surface of the base membrane, the porous layer comprises a polymer solid electrolyte and an oxide solid electrolyte, the oxide solid electrolyte is dispersed in the polymer solid electrolyte in a granular mode, and holes are further distributed in the polymer solid electrolyte. According to the diaphragm, on one hand, the difficulty of puncturing the diaphragm by lithium dendrites is improved by enhancing the mechanical strength of the diaphragm, on the other hand, the concentration polarization in the battery is reduced by improving the lithium ion transmission path, so that the difficulty of lithium dendrite growth is further increased, the diaphragm is not easy to puncture due to the mutual cooperation of the diaphragm and the lithium ion transmission path, and the cycle life of the battery is further prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, and a battery. Background Art

[0002] Lithium metal batteries have attracted much attention in the fields of 3C consumer batteries, energy storage, and electric vehicle batteries due to their high theoretical energy density. Lithium metal batteries are batteries that use lithium metal as the negative electrode. Lithium metal batteries mainly include liquid lithium metal batteries and solid lithium metal batteries. Among them, liquid metal batteries use electrolytes as electrolytes. As an intermediate transition form between lithium-ion batteries and solid-state lithium metal batteries, they have higher energy density than lithium-ion batteries, and the related processes are more mature than solid-state lithium metal batteries. They have recently received widespread attention from companies. However, existing liquid lithium metal batteries still have the following technical problems: In existing liquid lithium metal batteries, the growth of lithium dendrites may cause the diaphragm to be punctured, which in turn causes the battery to short-circuit and have a short cycle life. Summary of the invention

[0003] The embodiments of the present application provide a diaphragm and a method for preparing the same, and a battery, so as to at least partially solve the above-mentioned technical problems.

[0004] In order to achieve the above-mentioned purpose, according to the first aspect of the present application, a diaphragm is provided, which includes a base membrane and a porous layer located on at least one surface of the base membrane, the porous layer contains a polymer solid electrolyte and an oxide solid electrolyte, the oxide solid electrolyte is dispersed in the polymer solid electrolyte in a granular form, and the polymer solid electrolyte also has pores distributed in it.

[0005] Optionally, the porosity of the porous layer is 30% to 75%.

[0006] Optionally, the porous layer comprises 70 to 85 parts of the polymer solid electrolyte and 5 to 25 parts of the oxide solid electrolyte in parts by weight.

[0007] Optionally, the porous layer further comprises 2 to 5 parts of a binder and 0.05 to 2 parts of a dispersant, by weight.

[0008] Optionally, the porous layer contains 75 to 83 parts of the polymer solid electrolyte and 10 to 20 parts of the oxide solid electrolyte.

[0009] Optionally, when the porous layer further comprises a binder, the binder comprises at least one of polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, polyvinylidene fluoride, and polyurethane.

[0010] Optionally, when the porous layer further comprises a dispersant, the dispersant comprises at least one of polyethylene glycol, sodium polyacrylate, polyamide, polyvinyl alcohol, calcium carbonate, and silica powder.

[0011] Optionally, the polymer solid electrolyte includes an aramid-based polymer electrolyte.

[0012] Optionally, the aramid-based polymer electrolyte includes at least one of a meta-aramid electrolyte and a para-aramid electrolyte.

[0013] Optionally, the oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium lanthanum zirconium oxide.

[0014] Optionally, the average particle size of the oxide solid electrolyte is 0.1 μm to 1.5 μm.

[0015] Optionally, the base film includes at least one of a polypropylene base film, a polyethylene base film and a polyimide base film.

[0016] Optionally, the base film has a thickness of 3 μm to 30 μm and a porosity of 25% to 60%.

[0017] Optionally, the thickness of the porous layer is 0.5 μm to 5 μm.

[0018] Optionally, the separator includes a buffer layer, and the buffer layer is located on a surface of the porous layer facing away from the base membrane or on a surface of the base membrane facing away from the porous layer.

[0019] Optionally, the buffer layer includes a plurality of island-shaped elastic protrusions.

[0020] Optionally, the elastic protrusion comprises at least one of polyvinylidene fluoride and polymethyl methacrylate.

[0021] Optionally, the buffer layer has a thickness of 1 μm to 5 μm.

[0022] Optionally, the coating amount of the buffer layer is 0.2 g / m 2 ~0.8g / m 2 .

[0023] According to a second aspect of the present application, a method for preparing a diaphragm is provided, which is used to prepare the diaphragm as described above, and the method for preparing the diaphragm comprises: providing a basement membrane; Providing a first slurry, wherein the first slurry comprises a solvent, a pore former, a polymer solid electrolyte and an oxide solid electrolyte, wherein the polymer solid electrolyte is dissolved in the solvent; Performing a film-forming treatment on at least one surface of the base film with the first slurry to obtain a first wet film layer; The first wet film layer is subjected to a heating treatment so that the solvent is volatilized and the pore-forming agent is thermally decomposed, thereby obtaining a porous layer and further obtaining a separator.

[0024] Optionally, in parts by weight, the first slurry includes 160 to 265 parts of the solvent, 0.5 to 2 parts of the pore former, 70 to 85 parts of the polymer solid electrolyte and 5 to 25 parts of the oxide solid electrolyte.

[0025] Optionally, the first slurry further comprises 2 to 5 parts of a binder and 0.05 to 2 parts of a dispersant, measured by weight.

[0026] Optionally, the solid content of the first slurry is 25wt% to 65wt%.

[0027] Optionally, the pore-forming agent includes at least one of ammonium carbonate, ammonium bicarbonate, ammonium chloride, sodium carbonate and sodium bicarbonate.

[0028] Optionally, the first slurry further includes an auxiliary salt, which is dissolved in the solvent and is used to promote the dissolution of the polymer solid electrolyte in the solvent.

[0029] Optionally, the solvent is a polar solvent, and the polar solvent includes at least one of N-methylpyrrolidone, dimethylformamide and dimethyl sulfoxide.

[0030] Optionally, the auxiliary salt includes at least one of lithium chloride and calcium chloride.

[0031] Optionally, the mass ratio of the auxiliary salt to the solvent is 0.015-0.08.

[0032] According to a third aspect of the present application, a battery is provided, comprising the diaphragm as described above or a diaphragm prepared by the diaphragm preparation method as described above.

[0033] Optionally, the battery comprises a lithium metal battery, the lithium metal battery comprises a lithium metal negative electrode, the lithium metal negative electrode is located on one side of the diaphragm, and when the diaphragm comprises a buffer layer, the buffer layer is located between the lithium metal negative electrode and the porous layer.

[0034] Optionally, the lithium metal battery is a liquid lithium metal battery, and the diaphragm is soaked in electrolyte.

[0035] The diaphragm provided by the embodiment of the present application further adds a porous layer on the basis of the base film, and the porous layer is combined with the base film to increase the mechanical strength of the diaphragm, so that the diaphragm is not easily pierced by lithium dendrites. Further, the porous layer comprises a polymer solid electrolyte and an oxide solid electrolyte, wherein the polymer solid electrolyte is used as a substrate layer, and the oxide solid electrolyte is dispersed in the polymer solid electrolyte substrate layer as oxide solid electrolyte particles, so that the oxide solid electrolyte particles dispersed in the polymer solid electrolyte can be stacked with each other and form pores in the polymer solid electrolyte, and the polymer solid electrolyte is also distributed with holes, these pores and holes can be interconnected and form a circulation channel for electrolyte circulation, improve the wetting effect of the diaphragm on the electrolyte, and reduce the concentration polarization inside the diaphragm; at the same time, since the polymer solid electrolyte and the oxide solid electrolyte are both solid electrolytes containing lithium elements, they can conduct ions themselves, and the lithium ion conductivity of the diaphragm is further improved by introducing the polymer solid electrolyte and the oxide solid electrolyte into the surface of the base film through the porous layer. Improve the transmission of lithium ions. In this way, during the battery charging and discharging process, the electrolyte can first enter the diaphragm through the flow channel inside the porous layer. If the flow channel is a through channel that penetrates the porous layer, the electrolyte can directly reach the base membrane and infiltrate the base membrane, thereby forming a continuous ion transmission channel; for some non-through flow channels, lithium ions can also continue to be transmitted through the polymer solid electrolyte and the oxide solid electrolyte in the porous layer, so that lithium ions can quickly pass through the diaphragm during the charging and discharging process, reducing the concentration polarization inside the diaphragm and the concentration polarization on the surface of the diaphragm, thereby improving the concentration polarization on the surface of the negative electrode, thereby reducing the risk of lithium dendrite precipitation.

[0036] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0037] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings, wherein the same figure numbers represent the same parts in the following description.

[0038] Figure 1 A schematic diagram of the structure of the diaphragm is provided in Examples 1 to 7 and Comparative Examples 1 to 3 of the present application; Figure 2 A schematic diagram of the structure of the diaphragm provided in Example 8 of the present application; Figure 3 A schematic diagram of the structure of the diaphragm provided in Example 9 of the present application; Figure 4 A schematic diagram of the structure of the diaphragm provided in Example 10 of the present application; Figure 5 A schematic diagram of the structure of the diaphragm provided in Comparative Example 4 of the present application; Figure 6 A schematic diagram of the structure of the diaphragm provided in Comparative Example 5 of the present application; Figure 7 A schematic diagram of the structure of the diaphragm provided in Comparative Example 6 of the present application.

[0039] Description of reference numerals: 10-base film, 20-mixed coating, 201-first mixed coating, 202-second mixed coating, 30-buffer layer, 301-first buffer layer, 302-second buffer layer. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0041] According to the first aspect of the present application, a diaphragm is provided, which includes a base membrane and a porous layer located on at least one surface of the base membrane, the porous layer contains a polymer solid electrolyte and an oxide solid electrolyte, the oxide solid electrolyte is dispersed in the polymer solid electrolyte in a granular form, and pores are also distributed in the polymer solid electrolyte.

[0042] Oxide solid electrolyte is a compound composed of lithium, oxygen and other elements (such as phosphorus, titanium, aluminum, etc.). Polymer solid electrolyte is mainly composed of polymer matrix and lithium salt.

[0043] The diaphragm provided in the embodiment of the present application further adds a porous layer on the basis of the base membrane. The porous layer combined with the base membrane can increase the mechanical strength of the diaphragm, making the diaphragm not easily pierced by lithium dendrites.

[0044] Furthermore, the porous layer comprises a polymer solid electrolyte and an oxide solid electrolyte, wherein the polymer solid electrolyte serves as a substrate layer, and the oxide solid electrolyte serves as oxide solid electrolyte particles dispersed in the polymer solid electrolyte substrate layer, so that the oxide solid electrolyte particles dispersed in the polymer solid electrolyte can be stacked with each other and form pores in the polymer solid electrolyte, and there are also holes distributed in the polymer solid electrolyte, these pores and holes can be interconnected to form a flow channel for the electrolyte to flow, thereby improving the wetting effect of the diaphragm on the electrolyte and reducing the concentration polarization inside the diaphragm; at the same time, since both the polymer solid electrolyte and the oxide solid electrolyte are solid electrolytes containing lithium elements, they can conduct ions themselves, and by making the polymer solid electrolyte and the oxide solid electrolyte into a porous layer and introducing them into the surface of the base membrane, the lithium ion conductivity of the diaphragm is further improved, and the transmission of lithium ions is improved. In this way, during the battery charging and discharging process, the electrolyte can first enter the diaphragm through the flow channel inside the porous layer. If the flow channel is a through channel that penetrates the porous layer, the electrolyte can directly reach the base membrane and infiltrate the base membrane, thereby forming a continuous ion transmission channel; for some non-through flow channels, lithium ions can also continue to be transmitted through the polymer solid electrolyte and the oxide solid electrolyte in the porous layer, so that lithium ions can quickly pass through the diaphragm during the charging and discharging process, reducing the concentration polarization inside the diaphragm and the concentration polarization on the surface of the diaphragm, thereby improving the concentration polarization on the surface of the negative electrode, thereby reducing the risk of lithium dendrite precipitation.

[0045] That is, the diaphragm provided in the embodiment of the present application, on the one hand, increases the difficulty of lithium dendrites piercing it by enhancing its own mechanical strength, and on the other hand, reduces the concentration polarization inside the battery by improving the lithium ion transmission path, thereby increasing the difficulty of lithium dendrite growth. The two cooperate with each other, making the diaphragm not easily pierced, thereby improving the cycle life of the battery.

[0046] In some embodiments, the porosity of the porous layer is 30% to 75%. It is understood that the porosity of the porous layer will affect the mechanical strength of the porous layer and the wetting effect on the electrolyte. If the porosity of the porous layer is too large, the mechanical strength of the porous layer will decrease, and if the porosity of the porous layer is too small, the difficulty of the electrolyte passing through the porous layer will decrease, thereby making the base membrane not easily infiltrated by the electrolyte. By controlling the porosity of the porous layer to 30% to 75%, the mechanical strength of the diaphragm is improved as much as possible on the basis of making the diaphragm have a good electrolyte infiltration effect, and the risk of the diaphragm being punctured by lithium dendrites is reduced. As an example, the porosity of the porous layer is 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%.

[0047] In some embodiments, the porous layer contains 70 to 85 parts of polymer solid electrolyte and 5 to 25 parts of oxide solid electrolyte by weight. It can be understood that in the porous layer, the polymer solid electrolyte serves as the substrate layer, and the oxide solid electrolyte is dispersed in the polymer solid electrolyte as oxide solid electrolyte particles. Although the oxide solid electrolyte has better hardness and thermal stability than the polymer solid electrolyte, the mechanical properties and heat resistance of the diaphragm can be improved by increasing the oxide solid electrolyte, but the oxide solid electrolyte needs to rely on the polymer solid electrolyte to fix it and polymerize it together, that is, the polymer solid electrolyte provides cohesion for the formation of the porous layer, and increasing the polymer solid electrolyte can also improve the structural stability and toughness of the porous layer. Therefore, by controlling the content of the polymer solid electrolyte in the porous layer to 70 to 85 parts and the oxide solid electrolyte to 5 to 25 parts, not only can the porous layer have sufficient structural stability, but also the porous layer can have higher mechanical strength and heat resistance. As an example, the mass fraction of the polymer solid electrolyte in the porous layer is 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts or 85 parts; the mass fraction of the oxide solid electrolyte in the porous layer is 5 parts, 10 parts, 15 parts, 20 parts or 25 parts.

[0048] In some embodiments, the porous layer contains 75 to 83 parts of a polymer solid electrolyte and 10 to 20 parts of an oxide solid electrolyte. The mechanical properties and heat resistance of the porous layer can be further improved by further controlling the content of the polymer solid electrolyte and the oxide solid electrolyte in the porous layer. As an example, the mass fraction of the polymer solid electrolyte in the porous layer is 75, 76, 77, 78, 79, 80, 81, 82 or 83 parts; the mass fraction of the oxide solid electrolyte in the porous layer is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts.

[0049] In some embodiments, the porous layer further comprises 2 to 5 parts of a binder by weight. By adding a binder, the effect of bonding between oxide solid electrolytes and between oxide solid electrolytes and polymer solid electrolytes can be improved, and the mechanical strength and structural stability of the porous layer can be improved. As an example, the mass fraction of the binder in the porous layer is 2 parts, 3 parts, 4 parts or 5 parts. As an example, the binder includes at least one of polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, polyvinylidene fluoride, and polyurethane.

[0050] In some embodiments, the porous layer further comprises 0.05 to 2 parts of a dispersant by weight. The dispersant can be used to enhance the dispersion effect of the oxide solid electrolyte in the polymer solid electrolyte, thereby improving the overall mechanical properties of the diaphragm and the wetting effect on the electrolyte. As an example, the mass fraction of the dispersant in the porous layer is 0.05, 0.1, 0.5, 1, 1.5 or 2 parts. As an example, the dispersant includes at least one of polyethylene glycol, sodium polyacrylate, polyamide, polyvinyl alcohol, calcium carbonate, and silica powder.

[0051] In some embodiments, the polymer solid electrolyte includes an aramid-based polymer electrolyte. Aramid-based polymer electrolyte refers to a solid electrolyte material composed of aramid as a polymer matrix and a lithium salt. Aramid-based polymer electrolyte has the characteristics of good heat resistance, which can increase the rupture temperature of the diaphragm and reduce the risk of fire and explosion when the battery is punctured by a hot needle. It can be understood that when the diaphragm is punctured by a hot needle (i.e., a needle-like structure with a higher temperature), the base film is usually easily melted by the temperature brought by the hot needle to produce a first perforation, and the polymer solid electrolyte in the porous layer is also melted by the temperature brought by the hot needle to produce a second perforation. The second perforation corresponds to the first perforation, so that the positive and negative electrodes in the battery are easily contacted through the first perforation and the second perforation, resulting in a short circuit and then causing the battery to catch fire or explode; then due to the good heat resistance of the aramid-based polymer electrolyte, the heat resistance of the porous layer is also improved, so that the aperture of the formed second perforation can be controlled to reduce the risk of the second perforation being enlarged. Even if the aperture of the first perforation is relatively large, since the aperture of the second perforation is relatively small, the probability of the positive and negative electrodes contacting through the first perforation and the second perforation can be reduced, thereby improving the hot needle puncture pass rate of the battery.

[0052] In some embodiments, the aramid-based polymer electrolyte includes at least one of a meta-aramid electrolyte and a para-aramid electrolyte. Both the meta-aramid electrolyte and the para-aramid electrolyte have good thermal stability, thereby improving the thermal needle penetration rate of the battery.

[0053] In some embodiments, the oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum titanium oxide (LLTO), and lithium lanthanum zirconium oxide (LLZO). LATP is a NASICON-type solid electrolyte. As an example, the chemical formula of LATP is Li 1.5 Al 0.5 Ti 1.5 (PO4)3 or Li 1.3 Al 0.3 Ti 1.7 (PO4)3. LLTO belongs to the perovskite structure. As an example, the chemical formula of LLTO is Li 0.5 La 0.5TiO3. The crystal structure of LLZO is a garnet structure, which is mainly composed of lithium (Li), lanthanum (La), zirconium (Zr) and oxygen (O). As an example, the chemical formula of LLZO is Li7La3Zr2O 12 LATP, LLTO and LLZO all have high ionic conductivity and good chemical stability, which are beneficial to improving the effect of lithium ion transmission by the separator.

[0054] In some embodiments, the average particle size of the oxide solid electrolyte is 0.1 μm to 1.5 μm. By controlling the average particle size of the oxide solid electrolyte, the oxide solid electrolyte can have a better dispersion effect in the polymer solid electrolyte, thereby ensuring the performance of the porous layer. Generally, if the average particle size of the oxide solid electrolyte is too large, the dispersibility of the oxide solid electrolyte will be reduced, while if the average particle size of the oxide solid electrolyte is too small, the oxide solid electrolyte will agglomerate, which will also affect the dispersion effect of the oxide solid electrolyte. As an example, the average particle size of the oxide solid electrolyte is 0.1 μm, 0.5 μm, 1.0 μm, 1.2 μm, 1.4 μm or 1.5 μm.

[0055] In some embodiments, the thickness of the porous layer is 0.5 μm to 5 μm. Generally, if the thickness of the porous layer is too large, it will be more difficult for lithium ions to pass through the porous layer, affecting the concentration polarization inside the battery, and then increasing the risk of lithium precipitation in the battery. If the thickness of the porous layer is too small, the mechanical strength of the diaphragm will be insufficient, and the risk of the diaphragm being pierced by lithium dendrites will increase. By controlling the thickness of the porous layer, the risk of the diaphragm being pierced by lithium dendrites in the battery can be reduced. As an example, the thickness of the porous layer is 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5 μm.

[0056] In some embodiments, the base film includes at least one of a polypropylene (PP) base film, a polyethylene (PE) base film, and a polyimide (PI) base film. In the diaphragm, the performance of the base film will affect the performance of the diaphragm, and the base film is a porous film that allows ions to pass through and has the function of retaining an electrolyte. Here, the base film can be a single-layer structure or a multi-layer composite structure. As an example, the base film includes only one of a polypropylene base film, a polyethylene base film, and a polyimide base film, or the base film includes two or three of a polypropylene base film, a polyethylene base film, and a polyimide base film.

[0057] In some embodiments, the thickness of the base film is 3 μm to 30 μm, and the porosity is 25% to 60%. By controlling the thickness and porosity of the base film, the separator can have good mechanical strength and electrolyte infiltration effect. As an example, the thickness of the base film is 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm; the porosity of the base film is 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0058] In some embodiments, the diaphragm includes a buffer layer, and the buffer layer is located on the surface of the side of the porous layer away from the base membrane or on the surface of the side of the base membrane away from the porous layer. It is understood that the buffer layer can be arranged on the porous layer or directly on the base membrane, but the buffer layer is not arranged between the base membrane and the porous layer. As an example, the base membrane has a first surface and a second surface opposite to each other, the porous layer is arranged on the first surface, and the buffer layer is arranged on the second surface; or the porous layer is arranged on the first surface and the second surface of the base membrane, and the buffer layer is arranged on the porous layer and away from the base membrane; or the porous layer is arranged on the first surface, the buffer layer is arranged on the porous layer, and the second surface is exposed. In the battery, the diaphragm is usually arranged between the positive electrode and the negative electrode to isolate the positive electrode and the negative electrode. By arranging the buffer layer, when the electrode expands, the buffer layer can buffer the electrode expansion, reducing the risk of the diaphragm being punctured by lithium dendrites due to strong confrontation between lithium dendrites and the diaphragm.

[0059] In some embodiments, the buffer layer includes a plurality of island-shaped elastic protrusions. That is, a large number of island-shaped elastic protrusions grow on the surface of the porous layer or the surface of the base film and form a buffer layer. As an example, the cross-section of the island-shaped elastic protrusions is semicircular, triangular, trapezoidal or square along the thickness direction of the buffer layer. It can be understood that there are gaps between the island-shaped elastic protrusions, so that these gaps can be formed to provide growth space for the deposition of lithium dendrites, alleviate the excessive growth of lithium dendrites and cause the diaphragm to be pierced, and improve the cycle life of the battery. In addition, compared to the continuous film-like buffer layer, the buffer layer is set to be composed of a plurality of island-shaped elastic protrusions, and the island-shaped elastic protrusions have better deformation ability, which can effectively improve the buffer performance of the buffer layer. As an example, the buffer layer can be prepared by spraying, and the buffer layer formed in this way is composed of a large number of island-shaped elastic protrusions. The gaps between the island-shaped elastic protrusions can also be formed as channels for the circulation of electrolytes, which promote the infiltration of electrolytes into the diaphragms.

[0060] In some embodiments, the elastic protrusion comprises at least one of polyvinylidene fluoride and polymethyl methacrylate. That is, the material of the elastic protrusion can be polyvinylidene fluoride, polymethyl methacrylate, or polyvinylidene fluoride and polymethyl methacrylate. These materials usually have a certain degree of adhesion, and when the separator is used in a battery, the buffer layer can also be bonded to the electrode.

[0061] In some embodiments, the thickness of the buffer layer is 1 μm to 5 μm. It is understood that when the buffer layer includes a plurality of elastic protrusions, the average height of the elastic protrusions is equal to the thickness of the buffer layer. By controlling the thickness of the buffer layer, the diaphragm has both better buffering effect and ion transmission performance. As an example, the thickness of the buffer layer can be 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0062] In some embodiments, the coating amount of the buffer layer is 0.2 g / m 2 ~0.8g / m 2 As an example, the coating amount of the buffer layer can be 0.2 g / m 2 , 0.3g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 , 0.7g / m 2 or 0.8g / m 2 .

[0063] According to a second aspect of the present application, a method for preparing a diaphragm is provided, which is used to prepare the diaphragm as described above, and the method for preparing the diaphragm comprises: S1. providing a basement membrane; S2. providing a first slurry, wherein the first slurry comprises a solvent, a pore-forming agent, a polymer solid electrolyte and an oxide solid electrolyte, wherein the polymer solid electrolyte is dissolved in the solvent; S3, performing a film-forming treatment on at least one surface of the base film with the first slurry to obtain a first wet film layer; S4, heating the first wet film layer to volatilize the solvent and thermally decompose the pore-forming agent, thereby obtaining a porous layer and further obtaining a separator.

[0064] In the preparation method of the diaphragm provided in the embodiment of the present application, since the first slurry used to prepare the first wet film layer includes a mixed solvent, a pore-forming agent, a polymer solid electrolyte and an oxide solid electrolyte, wherein the polymer solid electrolyte is dissolved in the solvent, when the first wet film layer is heated, the solvent evaporates so that the polymer solid electrolyte precipitates, solidifies and forms a substrate layer, and in the process of solidification of the polymer solid electrolyte, not only the oxide solid electrolyte dispersed in the polymer solid electrolyte is solidified in the polymer solid electrolyte, but the pore-forming agent is also thermally decomposed simultaneously, so that the position originally filled by the pore-forming agent will leave holes in the polymer solid electrolyte, thereby converting the first wet film layer into a porous layer, and the porous layer is combined with the base film to obtain a diaphragm.

[0065] The preparation method of the diaphragm provided in the embodiment of the present application is not only simple, but also the prepared diaphragm has strong mechanical strength on the one hand, thereby increasing the difficulty of lithium dendrites piercing it. On the other hand, the diaphragm can also improve the path of lithium ion transmission, thereby reducing the concentration polarization inside the battery, thereby increasing the difficulty of lithium dendrite growth. The two cooperate with each other, making the diaphragm not easily pierced, thereby improving the cycle life of the battery.

[0066] In some embodiments, the first slurry includes 160 to 265 parts of solvent, 0.5 to 2 parts of pore former, 70 to 85 parts of polymer solid electrolyte and 5 to 25 parts of oxide solid electrolyte by weight. Within this ratio range, the polymer solid electrolyte is effectively dissolved in the solvent, and the oxide solid electrolyte and the pore former are uniformly mixed with the polymer solid electrolyte, so that in the prepared porous layer, the oxide solid electrolyte and the pores can be uniformly dispersed in the polymer solid electrolyte. As an example, in the first slurry, the mass fraction of the solvent can be 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts, 240 parts, 250 parts or 265 parts, the mass fraction of the pore former can be 0.5 parts, 1.0 parts, 1.5 parts or 2 parts, the mass fraction of the polymer solid electrolyte can be 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 72 parts, 74 parts or 85 parts, and the mass fraction of the oxide solid electrolyte can be 5 parts, 10 parts, 15 parts, 20 parts or 25 parts.

[0067] In some embodiments, the first slurry further comprises 2 to 5 parts of a binder and 0.05 to 2 parts of a dispersant by weight. As an example, in the first slurry, the weight percentage of the binder may be 2, 3, 4 or 5 parts, and the weight percentage of the dispersant may be 0.05, 0.1, 0.5, 1.0, 1.5 or 2 parts.

[0068] In some embodiments, the solid content of the first slurry is 25wt% to 65wt%. As an example, the solid content of the first slurry is 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt% or 65wt%. By controlling the solid content of the first slurry, the forming effect of the first wet film layer can be improved, thereby improving the forming effect of the porous layer.

[0069] In some embodiments, the pore-forming agent includes at least one of ammonium carbonate, ammonium bicarbonate, ammonium chloride, sodium carbonate and sodium bicarbonate. By using carbonates or ammonium salts as pore-forming agents, these substances usually have low thermal decomposition temperatures, so that a lower temperature can be used to convert the first wet film layer into a porous layer, reducing the risk of high temperature damaging the structure and chemical properties of the polymer solid electrolyte and the oxide solid electrolyte; in addition, these substances are mainly decomposed into gas after thermal decomposition, and the gas can be discharged from the porous layer, reducing the adverse effects of residual substances on the porous layer.

[0070] In some embodiments, the first slurry further includes an auxiliary salt, which is dissolved in a solvent, and the auxiliary salt is used to promote the dissolution of the polymer solid electrolyte in the solvent. By adding an auxiliary salt to the solvent to promote the dissolution of the polymer solid electrolyte in the solvent, on the one hand, the amount of solvent can be reduced, and on the other hand, the time for making the first slurry and the time for drying the first wet film layer can be shortened, thereby reducing the production cost of the diaphragm. As an example, the auxiliary salt includes at least one of lithium chloride and calcium chloride.

[0071] In some embodiments, the solvent is a polar solvent. The polar solvent can promote the rapid dissolution of the polymer solid electrolyte. In particular, when the polymer solid electrolyte is an aramid-based polymer electrolyte, the polar solvent can enhance the dissolution effect of the aramid-based polymer electrolyte. Optionally, the polar solvent is an organic polar solvent. As an example, the polar solvent includes at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide dimethyl sulfoxide.

[0072] In some embodiments, the mass ratio of the auxiliary salt to the solvent is 0.015 to 0.08. As an example, the mass ratio of the auxiliary salt to the solvent is 0.015, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07 or 0.08.

[0073] According to a third aspect of the present application, a battery is provided, comprising the diaphragm as described above or a diaphragm prepared by the diaphragm preparation method as described above.

[0074] In some embodiments, the battery includes a lithium metal battery, the lithium metal battery includes a lithium metal negative electrode, the lithium metal negative electrode is located on one side of the diaphragm, and when the diaphragm includes a buffer layer, the buffer layer is located between the lithium metal negative electrode and the porous layer. In this case, the buffer layer can also block the lithium metal negative electrode and the porous layer, reducing the risk of direct contact between the lithium metal negative electrode and the porous layer, thereby reducing the risk of the oxide solid electrolyte in the porous layer being reduced by lithium metal, especially when the oxide solid electrolyte includes LATP, the risk of tetravalent titanium in LATP being reduced to trivalent titanium by lithium metal can be effectively reduced, thereby improving the stability of LATP and the stability of the performance of the porous layer.

[0075] In some embodiments, the lithium metal battery is a liquid lithium metal battery, and the separator is soaked in an electrolyte. A liquid lithium metal battery refers to a battery whose negative electrode is a lithium metal negative electrode and contains an electrolyte.

[0076] The following is a description with reference to specific embodiments.

[0077] 1. Preparation of diaphragm Example 1 S1. Prepare a first slurry. The composition of the first slurry is shown in Table 1.

[0078] Table 1

[0079] In Example 1, the average particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %. It should be noted that in this application, the solid content of the first slurry is calculated as follows: solid content of the first slurry = (mass of polymer solid electrolyte + mass of oxide solid electrolyte + mass of binder + mass of dispersant + mass of pore former) / total mass of the first slurry × 100%.

[0080] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 4000 r / min for 10 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 4000 r / min, mixing evenly, to obtain a first slurry.

[0081] S2. Preparation of diaphragm, see Figure 1 , the preparation process of the diaphragm includes: S21, providing a base film 10, wherein the base film 10 is a polyethylene base film; the polyethylene base film has a thickness of 9 μm and a porosity of 40%; S22, coating the prepared first slurry onto one side surface of the base film 10 by micro gravure extrusion coating process, and then baking at 60° C. for 140 min, and cooling to form a mixed coating 20 (i.e., a porous layer) with a single layer thickness of 3 μm on the surface of the base film 10; S23, on the surface of the mixed coating, the coating amount is 0.5g / m 2 The buffer layer 30 (specifically a polyvinylidene fluoride coating) is sprayed, and then baked at a temperature of 60° C. for 140 minutes and cooled to obtain a diaphragm.

[0082] Example 2 The difference between Example 2 and Example 1 is that step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 2.

[0083] Table 2

[0084] In Example 2, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0085] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 500 r / min for 20 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 1000 r / min, mixing evenly, to obtain a first slurry.

[0086] The rest is the same as Example 1.

[0087] Example 3 The difference between Example 3 and Example 1 is step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 3.

[0088] Table 3

[0089] In Example 3, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0090] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, stir at a temperature of 100° C. and a stirring rate of 8000 r / min for 1 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 8000 r / min, mixing evenly, to obtain a first slurry.

[0091] Example 4 The difference between Example 4 and Example 1 is that step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 4.

[0092] Table 4

[0093] In Example 4, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0094] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, stir at a temperature of 100° C. and a stirring rate of 6000 r / min for 5 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 6000 r / min, mixing evenly, to obtain a first slurry.

[0095] Example 5 The difference between Example 5 and Example 1 is step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 5.

[0096] Table 5

[0097] In Example 5, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0098] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 2000 r / min for 15 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 2000 r / min, mixing evenly, to obtain a first slurry.

[0099] Example 6 The difference between Example 6 and Example 1 is step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 6.

[0100] Table 6

[0101] In Example 6, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0102] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 4000 r / min for 10 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 4000 r / min, mixing evenly, to obtain a first slurry.

[0103] Example 7 The difference between Example 7 and Example 1 is step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 7.

[0104] Table 7

[0105] In Example 7, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0106] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 4000 r / min for 10 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 4000 r / min, mixing evenly, to obtain a first slurry.

[0107] Example 8 S1. Prepare a first slurry. The composition of the first slurry is shown in Table 8.

[0108] Table 8

[0109] In Example 8, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 38.1 wt %.

[0110] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 4000 r / min for 10 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 4000 r / min, mixing evenly, to obtain a first slurry.

[0111] S2. Preparation of diaphragm, see Figure 2 , the preparation process of the diaphragm includes: S21, providing a base film 10, wherein the base film 10 is a polypropylene base film; the polypropylene base film has a thickness of 3 μm and a porosity of 32%; S22, applying the prepared first slurry to both surfaces of the base film 10 by a micro-gravure extrusion coating process, and then baking at a temperature of 40° C. for 240 minutes and cooling; forming a mixed coating 20 (i.e., a porous layer) on both surfaces of the base film 10, including a first mixed coating 201 and a second mixed coating 202, the thickness of the first mixed coating 201 is 2.5 μm, and the thickness of the second mixed coating 202 is 2.5 μm; S23, spraying a buffer layer 30 (specifically a polymethyl methacrylate coating) on ​​both the first mixed coating 201 and the second mixed coating 202 of the base film 10, including a first buffer layer 301 and a second buffer layer 302; the coating amount of the first buffer layer 301 is 0.25 g / m 2 The coating amount of the second buffer layer 302 is 0.25 g / m 2 , then baked at 40°C for 240 min, and cooled to obtain a diaphragm.

[0112] Example 9 The difference between Example 9 and Example 1 is step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 9.

[0113] Table 9

[0114] In Example 9, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.6 wt %.

[0115] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 4000 r / min for 10 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 4000 r / min, mixing evenly, to obtain a first slurry.

[0116] S2. Preparation of diaphragm, see Figure 3 , the preparation process of the diaphragm includes: S21, providing a base film 10, wherein the base film 10 is a PP / PE / PP three-layer co-extruded base film; the base film 10 has a thickness of 30 μm and a porosity of 45%; S22, applying the prepared first slurry to both surfaces of the base film 10 by micro-gravure extrusion coating process, and then baking at a temperature of 80° C. for 30 minutes and cooling; forming a mixed coating 20 (i.e., a porous layer) on both surfaces of the base film 10, including a first mixed coating 201 and a second mixed coating 202, the thickness of the first mixed coating 201 is 2.5 μm, and the thickness of the second mixed coating 202 is 2.5 μm; S23, on the surface of the first mixed coating 201 of the base film 10, the coating amount is 0.6 g / m 2 A buffer layer 30 is sprayed (specifically, polymethyl methacrylate and polyvinylidene fluoride are mixed in a mass ratio of 1:1 for coating), and the buffer layer 30 is not coated on the surface of the second mixed coating 202 of the base film 10, and then baked at a temperature of 80°C for 30 minutes and cooled; a diaphragm is obtained.

[0117] Example 10 The difference between Example 10 and Example 1 is step S1: S1. Prepare a first slurry. The composition of the first slurry is shown in Table 10.

[0118] Table 10

[0119] In Example 10, the particle size of the oxide solid electrolyte is 0.6 μm, and the solid content of the first slurry is 33.3 wt %.

[0120] The steps of preparing the first slurry include: S11, first add the polymer solid electrolyte into the mixed solution to dissolve, and stir at a temperature of 100° C. and a stirring rate of 4000 r / min for 10 h to form a polymer electrolyte solution; S12, adding the oxide solid electrolyte, binder, dispersant and pore-forming agent into the polymer electrolyte solution, stirring at room temperature at a stirring rate of 4000 r / min, mixing evenly, to obtain a first slurry.

[0121] S2. Preparation of diaphragm, see Figure 4 , the preparation process of the diaphragm includes: S21, providing a base film 10, wherein the base film 10 is a polyimide base film; the polyimide base film has a thickness of 15 μm and a porosity of 60%; S22, applying the prepared first slurry to one surface of the base film 10 by a micro-gravure extrusion coating process, and then baking at a temperature of 50° C. for 100 min, and cooling; forming a mixed coating 20 with a thickness of 4 μm on the surface of the base film 10; S23, on the surface of the mixed coating 20, the coating amount is 0.2g / m 2Spray the first buffer layer 301 (specifically a polymethyl methacrylate coating) on ​​the other surface of the base film 10 that is not coated with the mixed coating 20 at a coating amount of 0.2 g / m 2 The second buffer layer 302 (specifically a polymethyl methacrylate coating) is sprayed, then baked at a temperature of 50° C. for 100 minutes, and cooled; thus, a separator is obtained.

[0122] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the first slurry does not contain an oxide solid electrolyte. The other aspects are the same as Example 1.

[0123] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the first slurry does not contain a pore-forming agent. The other aspects are the same as those of Example 1.

[0124] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the first slurry does not contain an oxide solid electrolyte and a pore-forming agent. The other parts are the same as Example 1.

[0125] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the buffer layer 30 is not provided in the diaphragm, and the structure of the obtained diaphragm is as follows: Figure 5 The rest is the same as that of Example 1.

[0126] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the mixed coating 20 is not provided in the diaphragm, and the structure of the obtained diaphragm is as follows: Figure 6 The rest is the same as that of Example 1.

[0127] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the buffer layer 30 and the mixed coating 20 are not provided in the diaphragm, that is, the diaphragm only includes the base film 10, and the structure of the obtained diaphragm is as follows: Figure 7 The rest is the same as that of Example 1.

[0128] 2. The following performance tests were performed on the diaphragms prepared in Examples 1 to 10 and Comparative Examples 1 to 6, and the results are recorded in Table 11: 1. Puncture strength: Use a universal tensile testing machine with a 1 mm diameter needle moving downward at a rate of 200 mm / min and record the maximum force used to puncture the diaphragm.

[0129] 2. 130℃ / 0.5h heat shrinkage: Cut the diaphragm into a rectangular sample of 120mm×60mm, use a 100mm×50mm rectangular printing tool to cover it with a 100mm×50mm rectangle, clamp the sample between two A4 papers, fix it and bake it in a 130℃ forced air drying oven for 0.5h, measure the length and width of the rectangle after baking, and calculate its heat shrinkage rate = (size before baking - size after baking) / size before baking × 100%.

[0130] 3. Pore volume ratio inside the coating: The isopropanol penetration method is used to test the permeation volume per unit area of ​​the diaphragm to test the pore channel porosity of the coating (the coating here refers to the coating other than the base membrane). First, the mass m0 of the diaphragm is weighed, and then the diaphragm is placed in an isopropanol solution. After the isopropanol solution is completely infiltrated into the pores of the diaphragm coating, the diaphragm is taken out and the mass m1 of the diaphragm is measured. The mass m2 of isopropanol adsorbed by the diaphragm coating can be calculated. The mass m of isopropanol adsorbed by the base membrane can be obtained by the same method. 基膜 , the volume percentage of pores and channels inside the coating is calculated by calculating the mass of isopropanol adsorbed by the diaphragm coating: The mass of isopropanol adsorbed by the coating is m2=m1-m0-m 基膜 ; The volume ratio of pores and channels inside the coating = (mass m2 of isopropyl alcohol adsorbed by the coating / density of isopropyl alcohol) / volume of the entire coating × 100%.

[0131] 4. The electrolyte infiltration test method is: use a pipette to take a certain amount of 10μL of electrolyte and drop it on the surface of the diaphragm, and record the diameter of the electrolyte diffusion within 30s.

[0132] 5. Conductivity of isolated lithium ions: Assemble copper foil / diaphragm / copper foil symmetrical cells, test the impedance of 1-4 layers of separators at 25°C, 100k~0.01H, and calculate the ionic conductivity of the separator by linear fitting formula: σ=d / (R×S), where σ is the ionic conductivity, d is the thickness of the separator, R is the resistance of a single-layer separator, and S is the effective area for lithium ions to pass through the separator.

[0133] Table 11

[0134] 3. Preparation of batteries The diaphragms prepared in Examples 1 to 10 and Comparative Examples 1 to 6 are respectively applied to NCM523 system ternary positive electrode lithium metal batteries, NCM622 system ternary positive electrode lithium metal batteries and NCM811 system ternary positive electrode lithium metal batteries. When the diaphragms are in use, the surface coated with the buffer layer 30 is close to the negative electrode. If one surface of the base film 10 is coated with the mixed coating 20 and the buffer layer 30, and the other surface of the base film 10 is only coated with the buffer layer 30, then only the surface coated with the buffer layer 30 is close to the negative electrode.

[0135] 4. The following performance tests were performed on the batteries prepared using the diaphragms prepared in Examples 1 to 10 and Comparative Examples 1 to 6, and the results are recorded in Table 12: 1. 130℃ hot box test pass rate: Charge the battery to full charge at 0.2C rate, then place it in a 130℃ oven for 1h, observe the fire state at 30min, and the explosion state at 60min. If there is no fire or explosion, it means it has passed.

[0136] 2. Needle puncture pass rate: Charge the battery to full charge at a rate of 0.2C, pierce the battery cell with a 0.8mm needle at a rate of 200mm / min, and observe the fire and explosion of the battery cell. If the battery cell does not catch fire or explode after puncture, it means it has passed.

[0137] 3. Cycle life (number of cycles): In a constant temperature oven at 25°C, charge and discharge at a rate of 0.33C / 1C, and record the number of cycles with a capacity retention rate ≤80%.

[0138] Table 12

[0139] (1) The membranes in Examples 1 to 10 of the present application are based on the base film 10 by designing a coating structure, and preparing a porous layer on the surface of the base film 10 after mixing a polymer solid electrolyte, an oxide solid electrolyte, a pore-forming agent, and a solvent, which reduces the 130°C / 0.5h thermal shrinkage of the membrane from 7% to less than 3.5%, increases the 130°C hot box test pass rate from 20% to 100%, and increases the needle puncture pass rate from 0 to 100%. Compared with Comparative Examples 1 to 6, the membranes in Examples 1 to 10 of the present application have improved overall thermal shrinkage, hot box test, and needle puncture test.

[0140] (2) In the NCM523 ternary positive electrode material system, the cycle life of the diaphragms in Examples 1 to 10 of the present application is increased from 145 cycles to more than 190 cycles compared with the diaphragms in Comparative Examples 1 to 6. The main reason is that the combination of the oxide solid electrolyte, the pore-forming agent and the solvent in the mixed coating 20 forms a large number of pores and channels in the polymer solid electrolyte. After the structural design of the mixed coating 20 of the diaphragm is modified, its electrolyte wettability is increased, and the mixed coating 20 is a three-dimensional network structure. The pore structure and the channel structure are relatively uniform, and the pore connectivity is good, and the channel tortuosity is high. First, it can improve the transmission of lithium ions, improve the uniform passage of lithium ions, and achieve uniform current density. Second, when lithium dendrites grow, the growth path of lithium dendrites can be extended, and the growth of lithium dendrites can be delayed, which causes the diaphragm to be pierced, thereby delaying the occurrence of short circuit between the positive and negative electrodes, thereby improving the cycle life of the battery. In addition, the introduction of oxide solid electrolytes in the mixed coating 20, especially the introduction of LATP, LLTO, and LLZO, because LATP, LLTO, and LLZO can conduct ions themselves, after being introduced into the polymer solid electrolyte, the improvement of lithium ion conductivity is further improved, so that lithium ions can quickly pass through the diaphragm during the charge and discharge process, reduce the generation of concentration polarization, and prevent the generation of lithium dendrites induced by uneven current density. At the same time, the introduction of the buffer layer 30 is equivalent to setting a buffer layer for the growth of lithium dendrites, which can provide sufficient space for the growth of lithium dendrites, induce the uniform deposition of lithium dendrites, prevent the puncture of the diaphragm, thereby avoiding the phenomenon of positive and negative contact short circuit, and further improve the long-term cycle performance of lithium metal batteries.

[0141] In Examples 1 to 10, the design of the mixed layer structure of the polymer solid electrolyte and the oxide solid electrolyte and the use of the buffer layer 30 prolong the time for the diaphragm to be punctured due to the growth of lithium dendrites, and the cycle life is longer than that of Comparative Examples 1 to 6; Compared with Examples 5 and 6, due to the increase in the oxide solid electrolyte component, the filling material inside the mixed coating 20 increases, the pores and pore structures increase, and its ion conductivity increases, and the cycle life increases.

[0142] In Examples 1 to 10, the introduction of LATP, LLTO, and LLZO enables lithium ions to pass quickly during the charge and discharge process, further inhibiting the growth of lithium dendrites, and further improving the cycle life. As the LATP, LLTO, and LLZO components increase, the ionic conductivity increases and the cycle life increases.

[0143] Compared with Example 1 and Comparative Example 1, no oxide solid electrolyte is added to the diaphragm slurry used in the mixed coating 20 in Comparative Example 1, and Example 1 adds an oxide solid electrolyte on the basis of Comparative Example 1. The introduction of the oxide solid electrolyte will form a pore structure and a channel structure in the mixed coating 20 due to the interface of the material itself and the mutual stacking of the oxide solid electrolyte particles, thereby increasing the volume proportion of the pores and channels inside the mixed coating 20, increasing the electrolyte wettability, increasing the needle puncture pass rate, increasing the ion conductivity of the diaphragm, and improving the cycle life.

[0144] Compared with Example 1 and Comparative Example 2, no pore-forming agent is added to the diaphragm slurry used in the mixed coating 20 in Comparative Example 2, while Example 1 adds a pore-forming agent on the basis of Comparative Example 2. The addition of the pore-forming agent will form small bubbles during the baking process and will be removed, thereby forming pores, which increases the volume proportion of the internal pores of the mixed coating 20, increases the wettability of the electrolyte, increases the ion conductivity of the diaphragm, increases the needle puncture pass rate, and improves the cycle life.

[0145] Compared with Example 1 and Comparative Example 3, the oxide solid electrolyte and pore former are not added to the diaphragm slurry used in the mixed coating in Comparative Example 3. Example 1 adds an oxide solid electrolyte and a pore former on the basis of Comparative Example 3. The introduction of the oxide solid electrolyte will form a pore structure in the mixed coating 20 due to the interface of the material itself and the mutual stacking of the oxide solid electrolyte particles. The addition of the pore former will form small bubbles during the baking process and will be removed, thereby forming a uniform pore structure. In addition, the pore structure formed by the part of the pore former will be with the oxide solid electrolyte. Pore ​​channels are formed between the pore structures formed between the oxide solid electrolyte and the polymer solid electrolyte. In addition, the use of the solvent further increases the pores and channels inside the mixed coating 20. Therefore, compared with Comparative Example 3, in Example 1, the simultaneous addition of the oxide solid electrolyte, the pore-forming agent and the solvent can significantly increase the volume proportion of the pores and channels inside the mixed coating 20. At the same time, the electrolyte wettability, needle puncture pass rate, ion conductivity of the diaphragm and the cycle life are greatly improved, indicating that the simultaneous use of the oxide solid electrolyte, the pore-forming agent and the solvent in the diaphragm slurry has a significant synergistic effect.

[0146] Compared with Example 1 and Comparative Example 4, the diaphragm in Comparative Example 4 is not coated with a buffer layer, while Example 1 adds a buffer layer on the basis of Comparative Example 4, which can better provide sufficient space for the deposition of lithium dendrites, alleviate the puncture of the diaphragm caused by excessive growth of lithium dendrites, and improve the cycle life of the battery cell.

[0147] Compared with Example 1 and Comparative Example 5, the diaphragm in Comparative Example 5 is not coated with the mixed coating 20, but only coated with the buffer layer 30. Example 1 is equivalent to adding the mixed coating 20 on the basis of Comparative Example 5. The introduction of the mixed coating 20 greatly improves the thermal stability of the diaphragm. It contains a large number of pores and channels inside, which is beneficial to improve the wettability of the electrolyte, and the oxide solid electrolyte particles can improve the ionic conductivity of the diaphragm. This not only improves the volume ratio of the pores and channels inside the mixed coating 20, the electrolyte wettability, thermal stability and ionic conductivity of the diaphragm, but also its hot box test pass rate and needle puncture pass rate are significantly improved, and the cycle life is also significantly improved.

[0148] Compared with Example 1 and Comparative Example 6, the base film in Example 1 is used as a diaphragm in Comparative Example 6, and Example 1 adds a mixed coating and a buffer layer on the basis of Example 6, which not only improves the thermal stability and electrolyte wettability of the diaphragm, thereby improving the ionic conductivity of the diaphragm, but also improves the hot box test and needle puncture pass rate of the battery cell, and the buffer layer 30 can better provide sufficient space for the deposition of lithium dendrites, alleviate the excessive growth of lithium dendrites and cause the diaphragm to be pierced, and the cycle life is improved. The cycle life of the diaphragm in Comparative Example 4 is 146 cycles, the cycle life of the diaphragm in Comparative Example 5 is 126 cycles, the cycle life of the diaphragm in Comparative Example 6 is 109 cycles, and the cycle life of the diaphragm in Example 1 is 193 cycles. Compared with Comparative Examples 4 to Comparative Examples 6, the cycle life of the diaphragm in Example 1 is significantly improved, indicating that the use of the mixed coating 20 and the buffer layer 30 has a significant synergistic effect, and the cycle life of the diaphragm is significantly improved.

[0149] Compared with Comparative Examples 1 to 3, the combined use of polymer solid electrolyte, oxide solid electrolyte, pore former and solvent in Example 1 significantly improves the needle puncture rate of the separator.

[0150] (3) The same effect is also found in the NCM622 and NCM811 ternary cathode material systems.

[0151] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A diaphragm, characterized in that: The diaphragm includes a base film and a porous layer located on at least one surface of the base film, the porous layer contains a polymer solid electrolyte and an oxide solid electrolyte, the oxide solid electrolyte is dispersed in the polymer solid electrolyte in a particle form, and pores are also distributed in the polymer solid electrolyte.

2. The diaphragm according to claim 1, characterized in that The porosity of the porous layer is 30% to 75%.

3. The diaphragm according to claim 1, characterized in that In terms of weight, the porous layer comprises 70 to 85 parts of the polymer solid electrolyte and 5 to 25 parts of the oxide solid electrolyte.

4. The diaphragm according to claim 3, characterized in that In parts by weight, the porous layer further comprises 2 to 5 parts of a binder and 0.05 to 2 parts of a dispersant; and / or, The porous layer contains 75 to 83 parts of the polymer solid electrolyte and 10 to 20 parts of the oxide solid electrolyte.

5. The diaphragm according to claim 3, characterized in that In the case where the porous layer further comprises a binder, the binder comprises at least one of polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, polyvinylidene fluoride, and polyurethane; and / or, In the case where the porous layer further comprises a dispersant, the dispersant includes at least one of polyethylene glycol, sodium polyacrylate, polyamide, polyvinyl alcohol, calcium carbonate, and silica powder.

6. The diaphragm according to any one of claims 1 to 5, characterized in that: The polymer solid electrolyte includes an aramid-based polymer electrolyte.

7. The diaphragm according to claim 6, characterized in that The aramid-based polymer electrolyte includes at least one of a meta-aramid electrolyte and a para-aramid electrolyte.

8. The diaphragm according to any one of claims 1 to 5, characterized in that The oxide solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium lanthanum zirconium oxide; and / or, The average particle size of the oxide solid electrolyte is 0.1 μm to 1.5 μm; and / or, The base film comprises at least one of a polypropylene base film, a polyethylene base film and a polyimide base film; and / or, The base film has a thickness of 3 μm to 30 μm and a porosity of 25% to 60%; and / or, The thickness of the porous layer is 0.5 μm to 5 μm.

9. The diaphragm according to any one of claims 1 to 5, characterized in that: The separator includes a buffer layer, and the buffer layer is located on a surface of the porous layer on a side away from the base film or on a surface of the base film on a side away from the porous layer.

10. The diaphragm according to claim 9, characterized in that The buffer layer includes a plurality of island-shaped elastic protrusions.

11. The diaphragm according to claim 10, characterized in that The elastic protrusion comprises at least one of polyvinylidene fluoride and polymethyl methacrylate; and / or, The thickness of the buffer layer is 1 μm to 5 μm; and / or, The coating amount of the buffer layer is 0.2 g / m 2 ~0.8g / m 2 .

12. A method for preparing a diaphragm, for preparing the diaphragm according to any one of claims 1 to 11, characterized in that: The preparation method of the diaphragm comprises: providing a basement membrane; Providing a first slurry, wherein the first slurry comprises a solvent, a pore former, a polymer solid electrolyte and an oxide solid electrolyte, wherein the polymer solid electrolyte is dissolved in the solvent; Performing a film-forming treatment on at least one surface of the base film with the first slurry to obtain a first wet film layer; The first wet film layer is subjected to a heating treatment so that the solvent is volatilized and the pore-forming agent is thermally decomposed, thereby obtaining a porous layer and further obtaining a separator.

13. The method for preparing a diaphragm according to claim 12, characterized in that: In parts by weight, the first slurry includes 160 to 265 parts of the solvent, 0.5 to 2 parts of the pore former, 70 to 85 parts of the polymer solid electrolyte and 5 to 25 parts of the oxide solid electrolyte.

14. The method for preparing a diaphragm according to claim 12 or 13, characterized in that: In parts by weight, the first slurry further comprises 2 to 5 parts of a binder and 0.05 to 2 parts of a dispersant; and / or, The solid content of the first slurry is 25wt% to 65wt%; and / or, The pore former includes at least one of ammonium carbonate, ammonium bicarbonate, ammonium chloride, sodium carbonate and sodium bicarbonate.

15. The method for preparing a diaphragm according to claim 12, characterized in that: The first slurry further includes an auxiliary salt, which is dissolved in the solvent and is used to promote the dissolution of the polymer solid electrolyte in the solvent.

16. The method for preparing a diaphragm according to claim 15, characterized in that: The solvent is a polar solvent, and the polar solvent includes at least one of N-methylpyrrolidone, dimethylformamide and dimethylacetamide dimethyl sulfoxide; and / or, The auxiliary salt comprises at least one of lithium chloride and calcium chloride; and / or, The mass ratio of the auxiliary salt to the solvent is 0.015-0.

08.

17. A battery, characterized in that: A diaphragm comprising the diaphragm according to any one of claims 1 to 11 or a diaphragm prepared by the method for preparing the diaphragm according to any one of claims 12 to 16.

18. The battery according to claim 17, characterized in that The battery comprises a lithium metal battery, the lithium metal battery comprises a lithium metal negative electrode, the lithium metal negative electrode is located on one side of the separator, and when the separator comprises a buffer layer, the buffer layer is located between the lithium metal negative electrode and the porous layer.

19. The battery according to claim 18, characterized in that The lithium metal battery is a liquid lithium metal battery, and the diaphragm is soaked in electrolyte.

Citation Information

Patent Citations

  • Separator and manufacturing method thereof, lithium battery including same, and method of manufacturing lithium battery

    CN104659311A

  • Organic-inorganic composite solid electrolyte isolating membrane, preparation method and semi-solid battery

    CN119050604A

  • Solid electrolyte and battery

    JP1997134739A

  • Separator for separating electrodes

    JP2001043842A

  • Separator and preparation method therefor and electrochemical device comprising separator

    WO2019157695A1

Cited By

  • Solid electrolyte membrane, preparation method and lithium ion battery

    CN120261679A